2016
DOI: 10.1007/s13277-015-4511-y
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of microRNA-31 targeting integrin α5 suppresses tumor cell invasion and metastasis by indirectly regulating PI3K/AKT pathway in human gastric cancer SGC7901 cells

Abstract: To verify the hypothesis that upregulation of microRNA-31 (miR-31) targeting integrin α5 (ITGA5) suppresses tumor cell invasion and metastasis by indirectly regulating phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway in human SGC7901 gastric cancer (GC) cells. The miRTarBase was used to predict whether ITGA5 is the target gene of miR-31, which was further confirmed by luciferase reporter gene assay. The SGC7901 GC cells were divided into five groups including the blank, miR-31 mimic, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…These results were in accordance with the study conducted by Xie et al [20] who found that ITGA5 could promote growth, migration, and invasion of esophageal squamous cell carcinoma (ESCC) cells. However, we also found that multiple miRNAs (except miR-330-5p) could also target ITGA5, including miR-128, miR-31, miR-26a, and miR-205 [23,25,33,34]. Several other factors could modulate the expression of ITGA5 as well.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results were in accordance with the study conducted by Xie et al [20] who found that ITGA5 could promote growth, migration, and invasion of esophageal squamous cell carcinoma (ESCC) cells. However, we also found that multiple miRNAs (except miR-330-5p) could also target ITGA5, including miR-128, miR-31, miR-26a, and miR-205 [23,25,33,34]. Several other factors could modulate the expression of ITGA5 as well.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies have indicated that ITGA5 can operate in certain cancers—including breast cancer, non-small cancer, and gastric cancer—by activating focal adhesion kinase to promote cell adhesion and migration [20,2224]. For example, Zhang et al [25] found that ITGA5 can work with miR-31 in affecting cell invasion and metastasis of gastric cancer. Although ITGA5 has been studied in several different malignancies, few researches have been conducted to evaluate its function and expression level in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…When considering all 37 infection-regulated miRNAs whose expression differed between the two mouse strains, nine miRNAs had targets that were significantly over-represented in the PI3K-Akt signaling pathway (DIANA tool). Five of these [miR-34b-3p, miR-34c-5p, miR-34b-5p, miR-92b-3p, and miR-182-5p; as well as miR-31-5p, which was identified through literature search (41)] belonged to the aforementioned seven miRNAs which were expressed more highly in the C57BL/6J mice and downregulated throughout the time course.…”
Section: Resultsmentioning
confidence: 99%
“…In gliomas, ADAMTS9-AS2 acts as a novel tumor suppressor that inhibits glioma cell metastasis. [25][26][27] The PI3K-Akt signaling pathway is involved in important functions such as growth, differentiation, invasion, and metastasis of gastric cancer cells. 23 In ovarian cancer, ADAMTS9-AS2 affects the progression of ovarian cancer by targeting the miR-182-5p/FOXF2 signaling pathway.…”
Section: Relationship Between Lncrnamentioning
confidence: 99%